2016
DOI: 10.1111/jce.12994
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Caliber Lead Failure After Generator Exchange

Abstract: According to our results, the preventive removal/replacement of the Sprint Fidelis leads with normal function until GE is not a recommended practice since the rate of dysfunction after the procedure in this subgroup is no different compared with other defibrillator leads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…79 Two series of patients with Fidelis leads reported conflicting results associated with generator exchange (20.8% failure rate after generator exchange vs 2.54% in matched controls, P,.001 in one study, and in another study a 3.6% incidence of lead failure after generator exchange compared with 3.5% in controls, P5.962). 80,81 The lead failure rate did not increase in the first year after generator exchange in a series of patients with Riata leads (1.5% vs 2%, P5.32). 82…”
Section: Risk Of Lead Failure After Generator Exchangementioning
confidence: 88%
“…79 Two series of patients with Fidelis leads reported conflicting results associated with generator exchange (20.8% failure rate after generator exchange vs 2.54% in matched controls, P,.001 in one study, and in another study a 3.6% incidence of lead failure after generator exchange compared with 3.5% in controls, P5.962). 80,81 The lead failure rate did not increase in the first year after generator exchange in a series of patients with Riata leads (1.5% vs 2%, P5.32). 82…”
Section: Risk Of Lead Failure After Generator Exchangementioning
confidence: 88%
“…Still, patients with a functioning SFL have a survival similar to patients with the nonadvisory Medtronic Quattro lead . In addition, Salgado et al demonstrated that the rate of failure after generator replacement was similar between functioning SF and other defibrillator leads (3.5 vs 3.6% after 1 year, P = .97), and insofar did not recommend preemptive lead replacement or removal.…”
Section: Discussionmentioning
confidence: 99%